2021
DOI: 10.1021/jacs.0c13350
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Induced Assembly and Coalescence of Lead Chalcogenide Nanocrystals

Abstract: We report here pressure induced nanocrystal coalescence of ordered lead chalcogenide nanocrystal arrays into one-dimensional (1D) and 2D nanostructures. In particular, atomic crystal phase transitions and mesoscale coalescence of PbS and PbSe nanocrystals have been observed and monitored in situ respectively by wide- and small-angle synchrotron X-ray scattering techniques. At the atomic scale, both nanocrystals underwent reversible structural transformations from cubic to orthorhombic at significantly higher p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In the setup, a Pilatus 100 K is used for wide-angle x-ray scattering (WAXS) and a MAR345 image plate ~ 3 m from sample is used for SAXS. Meng et al combined HP XRD and SAXS to characterize the structural and morphological changes in PbS and PbSe nanocrystals and demonstrated that the applied pressure induced a reversible atomic phase transition of the nanocrystals under hydrostatic pressure (Meng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the setup, a Pilatus 100 K is used for wide-angle x-ray scattering (WAXS) and a MAR345 image plate ~ 3 m from sample is used for SAXS. Meng et al combined HP XRD and SAXS to characterize the structural and morphological changes in PbS and PbSe nanocrystals and demonstrated that the applied pressure induced a reversible atomic phase transition of the nanocrystals under hydrostatic pressure (Meng et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among semiconductor NCs, PbS and PbSe are two of the most widely studied materials; they possess unique properties, including large Bohr radii of excitons, tunable absorption ranges, and focused emission colors, making them suitable for a wide range of emerging optoelectronic applications. Although the atomic phase behaviors of these lead-chacolgenide NCs of different shapes and sizes under high pressures have been thoroughly investigated, studies on ordered assembly at the mesoscale and pressure-induced coalescence are limited to a couple of reports on PbS nanospheres and nanocubes. , Meng et al recently reported the synthesis of 1.6 nm PbS spherical NCs and 12.1 nm PbSe nanocubes and their self-assembly into ordered arrays via slow solvent evaporation methods . Both NCs exist in RS crystal structures at ambient pressure and self-assemble into fcc superlattices.…”
Section: Pressure-induced Np Structural Transformation At the Mesoscalementioning
confidence: 99%
“…Morphologies of NCs after compression: (A) TEM images of 2D PbS NSs and lamellar structures (inset); (B) HRTEM image of the circled area in (A) and the corresponding FFT pattern (inset); (C, D) TEM and HRTEM images of 1D PbS short NWs; (E–H) TEM, HRTEM, and FFT (inset) images of 1D PbSe NRs. Reproduced with permission from ref . Copyright 2021 American Chemical Society.…”
Section: Pressure-induced Np Structural Transformation At the Mesoscalementioning
confidence: 99%
“…Hydrothermal synthesis of SiO 2 nanoparticles is the new technological method with a low production cost, high density of silanol groups, low toxicity, excluding the use of chemical reagents and other green chemistry methods of nanoparticle synthesis [ 1 , 2 , 3 ], and allows to obtain different forms of nanosilica—sols, gels, powders, products of the sol-gel process applied in concrete, agricultural plants, medicines, and other materials [ 4 , 5 , 6 , 7 ]. The technology of hydrothermal synthesis includes the stages of OSA polymerization, ultrafiltration membrane concentration of nanoparticles, the sol-gel process, vacuum sublimation, and others [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%